PEMIKIRAN HUKUM PROGRESIF: Otentisitas Pemikiran Berbasis Ideologis Ke-Indonesiaan - Khudzaifah Dimyati (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2015)
Why is the law that has the purpose to regulate social order, would lead to chaos in the community? There are two things that need to be observed, first, because the law narrowly conceived, which in turn tend to be formalistic, involutive, slow and lack of the capacity to adapt and anticipate the development of complex aspects of community life and progressive. This is the failure of positive law that could not see far ahead. Second, the attitude of law enforcement officials often ignore the public sense of justice with controversial and discriminative decisions.The implication of this phenomenon is the number of resistance legal product in the community. Laws experiencing poverty of Indonesian ideology substantively have lost the "spirit", which should be entailed by the law itself has gained fresh air when present progressive legal thought  presents in the middle of dialectical thinking in Indonesia law.